Influences of gadgets on students' learning achievement for early childhood - Indi Aminah; Elihami Elihami; Masnur Masnur (Sublim: Jurnal Pendidikan, 2022)
This research aims to determine how much influence gadgets have on the learning outcomes of early childhood students. This research is qualitative research. This research is carried out by collecting data in reasonable conditions by using work methods that are systematic, directed and responsible so that there is no essence in data collection activities or information that is reasonable. This indicates that the influence of the role of parents, students' learning motivation and the use of gadgets on student learning outcomes is powerful and significant.